Immuno Modulatory Potentials and Histopathological Effects of Aqueous Extract of Abrus Precatorius Leaf in Mus Musculus - Saganuwan, Saganuwan Alhaji; Onyeyili, Patrick Azubuike; Etuk, Emmanuel Udok (Journal of Hematology Research, 2014)
Aqueous extract of Abrus precatorius leaf is being used by Nupe community of Nigeria to treat infectious diseases including malaria, pneumonia, typhoid, diarrhoea, wound and candidiasis. The aim of the research was to study immunomodulatory potentials and histopathological effects of the extract. Forty-two mice of either sex weighing 28.25+5.92 g used for the study were divided into 6 groups of seven mice each administered 0, 12.5, 25, 50, 100 and 200 mg/kg bodyweight for a period of 3 weeks. The body weight and blood samples of the mice were obtained prior to the administration of the extract and subsequently weekly. One-third milliliter (0.33 ml) of blood was obtained from the tail vein of each mice and placed in ethylene diamine tetra acetate (EDTA) sample bottles for haematology. Liver, lung, spleen and heart were harvested for histopathology. Observed are significantly increased (p<0.05) packed cell volume (PCV), erythrocytes, lymphocytes, decreased neutrophils, monocytes, basophils and eosinophils. Histopathology revealed interstial haemorrhage and mononuclear cells infiltration of hepatocytes, thinning of alveolar septae and widening of alveolar spaces, myocarditis with mononuclear cells infiltration and moderate hyperplasia of white pulp of spleen. Hence, the plant may be used in the treatment of anaemia, asthma and immune-compromised diseased conditions. Abrus agglutinin and abrin have been responsible for immunomodulatory and cytotoxic activities of the plant respectively.